MORPHOFUNCTIONAL PURPOSE OF HUMAN ATRIAL AURICLES - Stepanchuk, A.P.; Royko, N.V.; Fylenko, B.M.; Pryshlyak, A.M. (World of Medicine and Biology, 2018)
The paper is aimed at the topography study of the normal human atrial auricles. Specimens of 24 human hearts of both gender aged 55 to 76 years old with no cardiovascular lesions in the history have been studied. The analysis of the findings has shown that the right atrial auricle area, due to the presence of pectineal muscles and fossae between them, is a special adaptation which, in systole, results in the formation of turbulent streams, overlapping the main blood flow from the right atrium in the ventricles, giving it some turbulence. The longitudinal axis of the left atrial auricle is oriented perpendicular to the axial flow of blood from the left atrium into the ventricle. Generally, this is similar to a special attachment, the purpose of which is to transform the rhythmic reductions of the pectineal muscles of the atrial auricle into the force necessary for lateral shifting of blood flow layers through the atrium to the left ventricle and giving it a turbulent movement. The interior topography of the right and left atrial auricles is irregular and such scalloped surface is formed by the pectineal muscles, trabecules, multiple fossae and rare diverticula-like cavities. The extra and intracorporal models of the artificial heart must have a topography of the plains as close as possible to the human heart to avoid cardiovascular complications. The size of the auricle and its orifice should be considered during surgery on the cardiac valves.
Keywords: atrial auricles; orifice; heart; pectineal muscles; trabeculae